A system of Science and Technology Parks for the Rome area. (1st January 1997) - Cricelli, Livio; Gastaldi, Massimo; Levialdi, Nathan
In this paper, starting from a survey of Rome industrial and scientific area, we attempt to provide a project hypothesis for the setting up of a "network" of Science and Technology Parks in Lazio. This network would provide a fundamental link between the firms (especially the SMEs) and the scientific base that are present in the Rome area. We propose a potential operational structure, based on the network enterprise concept, to enable the business and science worlds to achieve the proper degree of symbiosis